2014
DOI: 10.1158/1055-9965.epi-13-0779
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Drinking and Second Primary Cancer Risk in Patients with Upper Aerodigestive Tract Cancers: A Systematic Review and Meta-analysis of Observational Studies

Abstract: Background: We conducted a systematic review and meta-analysis of existing data from observational studies to assess the strength of the association of alcohol drinking with second primary cancer risk in patients with upper aerodigestive tract (UADT; oral cavity, pharynx, larynx, and esophagus) cancer.Methods: PubMed and Embase were searched up to July 2012 and the reference lists of studies included in the analysis were examined. Random-effects models were used to estimate summary relative risks (RR) and 95% … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 45 publications
2
41
0
1
Order By: Relevance
“…People who continue to smoke and/or consume higher amounts of alcohol after diagnosis have a worse prognosis . We found an association between being a current or former smoker at diagnosis and high alcohol consumption at 12 months, in agreement with a previous study .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…People who continue to smoke and/or consume higher amounts of alcohol after diagnosis have a worse prognosis . We found an association between being a current or former smoker at diagnosis and high alcohol consumption at 12 months, in agreement with a previous study .…”
Section: Discussionsupporting
confidence: 92%
“…Tobacco and alcohol consumption are established risk factors for developing head and neck cancer . Continued tobacco and alcohol consumption after treatment for head and neck cancer is a risk factor for the development of second primary cancers, and decreased 5‐year survival rates . Tobacco consumption during treatment is also associated with poorer outcomes of surgical and nonsurgical treatments .…”
Section: Introductionmentioning
confidence: 99%
“…Postdiagnosis lifestyle habits, including diet and alcohol consumption, have been associated with cancer prognosis, risk of recurrence or second cancer, and mortality4, 5, 6, 7 but also with quality of life 8. Tertiary prevention, by adopting and maintaining a healthy lifestyle, is crucial for reducing morbidity and mortality and improving the quality of life of cancer patients and survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, primary prevention of lung cancer is critical. Many studies have shown that lung cancer is associated with genetic factors34, and environmental factors including tobacco use5, alcohol consumption6, and intake of fruit, vegetables7 and vitamins89 can also affect the incidence of lung cancer.…”
mentioning
confidence: 99%